Analisis Perlindungan Hukum bagi Pelaku Usaha Penyedia Sistem Pembayaran Qris (Quick Response Indonesian Standard) berdasarkan Undang-Undang Nomor 8 Tahun 1999 - Rahayu, Titin Puji (Proceedings Series on Social Sciences & Humanities, 2024)
Technological developments have changed the paradigm of payment systems from cash to non-cash, including in the form of electronic money (e-money) and QR-Code. QR-Code has become a popular payment method, especially with the implementation of Quick Response Indonesian Standard (QRIS). However, with technological advances also come new challenges related to legal protection for businesses that provide QRIS payment systems. This paper discusses the urgency of legal protection for business actors providing QRIS payment systems based on Law Number 8 Year 1999 concerning Consumer Protection. In this context, the concepts of freedom of contract, consent, sale and purchase, and consumer protection are elaborated to understand the rights and obligations of the parties in electronic payment transactions. The importance of the application of law as a preventive and repressive measure to prevent and overcome violations is also discussed. In addition, the relationship with Law Number 19 of 2016 concerning Electronic Information and Transactions and the implementation of Bank Indonesia regulations related to QRIS are highlighted in enforcing the rules and ensuring security and legal certainty in electronic payment transactions.